Historic and contemporary anthropogenic effects on granulometry and species composition detected from sediment cores and death assemblages, Nelson Bays, Aotearoa-New Zealand. (1st November 2020) - Handley, Sean J.; Swales, Andrew; Horrocks, Mark; Gibbs, Max; Carter, Megan; Ovenden, Ron; Stead, Jon
Abstract: To effectively manage anthropogenic stressors causing widespread and pervasive habitat change, resource managers and policy makers require advice on priority stressors to optimally target conservation and restoration outcomes. This is difficult in soft sediment ecosystems affected by multiple stressors operating across centuries with possible legacy interactions. Using tools from the emerging discipline of conservation paleobiology, we attempted to disentangle the effects of two stressors: i) changes to sediments (sedimentation rate, composition) and ii) fishing disturbance across pre-human to contemporary timescales by analysing death assemblages (DA) at a rare location protected from power fishing methods for ca. 30 yr in Nelson Bays, Aotearoa-New Zealand. Replicate sediment cores and surface grab samples were collected at paired stations, spread across three depth profiles (25, 30, 35 m), split inside and outside the fishing exclusion zone. Sediment core geochronologies were established using radioisotope dating and analysis of terrestrial plant palynomorphs (spores, pollen, starch) associated with Māori and European introduction to Aotearoa-New Zealand. Results unearthed a complex of brachiopods, molluscs, crustacea, bryozoan, and Māori-introduced pollen and starch remains – the latter a marine first. Following human arrival in the region (ca.1500AD) statistical models revealed separation of DAs between time periods were correlated with a 10–15% increase in sediment silt content following a ca.11-fold increase in Sediment Accumulation Rates (SAR). In contrast, separation of recent surface DAs (ca. 60yr) are now more strongly correlated with sediment mixing, detected by discordance in radioisotope profiles, consistent with exposure to homogenising effects of fishing disturbance outside the exclusion zone. We conclude that historic legacy effects, ongoing sedimentation and fishing disturbance have synergistically modified the sediment characteristics from "natural" baseline conditions. Those changes have likely contributed to the collapse and lack of recovery of Nelson Bays shellfish fisheries. Highlights: We attempted to disentangle effects of sedimentation and fishing historically. Māori and European palynomorphs constrained core geochronologies. Māori-introduced cultigen artefacts were discovered – a marine first. Statistical models separated death assemblages from baseline conditions. Fishing disturbance accounted for greatest variation in modern assemblages.